Hansel and Gretel on Lanzarote: Neujahr, from Juli Zeh - Geck, Sabine (Revista de Filología Alemana, 2022)
This paper is about the fairy-tale elements in Zeh’s best-selling novel, especially in the central embedded story, this is, the main character’s early childhood memory when he and his younger sister were abandoned by their parents in a summer house on canary island Lanzarote. The summer holidays of the now adult on the same place are thus transformed in a journey into the subconscious which, to a certain point, resolves his psychological problems. The numerous parallels with Grimm’s fairy-tale Hansel and Gretel, not consciously intended by the author, are unveiled and their function explained in the context of the novel in order to get a psychological interpretation.
Keywords: Literary Motifs; Fairy Tales; Hansel and Gretel; Nixie Tales; Subconscious; Child Abandonment